Molecular pathogenesis of fibrosis in systemic sclerosis - Jinnin, Masatoshi (Trends in Immunotherapy, 2022)
The principal cause of fibrosis in systemic sclerosis is thought to be excessive deposition of extracellular matrix in multiple organs. The main component of matrix is thought to be collagen, especially type I collagen, which is one of the most abundant proteins in the mammalian body. Various factors have been estimated to be involved in the mechanism of their excessive deposition in fibrotic tissues of systemic sclerosis. In this review, we discuss the latest findings on these factors.